(untitled) (Journal of Hama University, 2020)
The research was conducted to study the effect of four concentrations of NaCl (50, 100, 150, 200 mM) on the growth of 5 varieties of in vitro potatoes. The increased concentration of salinity led to steadily increase of the EC and Ψ values. The measurements of growth indicators (length and diameter of stem, number of leaves, total plant area, root length, wet and dry weights) were performed on the plants of 45 days old. The greatest decrease of plant length (9 times) and number of leaves (4.41 times, were recorded in Kastelli variety in T4 treatment as compared to the control (16.11 cm and 14.33 leaves / plant, respectively). The greatest decrease of plant diameter (4.74 times) was recorded in Canbera variety in T4 treatment as compared to the control (1.99 mm). The T4 treatment in Rubma variety recorded the highest reduction of the plant area (27.43 times) as compared to the control (1934.006 mm2). Root death was recorded in Rubma variety at treatment T4, while in the same treatment in Canbera variety, the largest decrease of this root length was observed (35 times) as compared to the control (14 mm).Concerning the wet and dry weights, T4 treatment in Rubma and Spunta varieties was achieved the highest wet weight decrease (11.09 and 11.79 times) as compared to the control (0.588 and 1.191 g, respectively), and dry weight decrease (9.43 and 9.08 times) as compared to the control (0.066 and 0.109 g, respectively). The cluster analysis showed that Patricia variety was tolerant to stress, while the two varieties Rumba and Spunta are moderately tolerant, and Canbera and Kastelli are sensitive to stress salt.